2020
DOI: 10.1093/nar/gkaa1034
|View full text |Cite
|
Sign up to set email alerts
|

jMorp updates in 2020: large enhancement of multi-omics data resources on the general Japanese population

Abstract: In the Tohoku Medical Megabank project, genome and omics analyses of participants in two cohort studies were performed. A part of the data is available at the Japanese Multi Omics Reference Panel (jMorp; https://jmorp.megabank.tohoku.ac.jp) as a web-based database, as reported in our previous manuscript published in Nucleic Acid Research in 2018. At that time, jMorp mainly consisted of metabolome data; however, now genome, methylome, and transcriptome data have been integrated in addition to the enhancement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 47 publications
(42 reference statements)
1
96
0
Order By: Relevance
“…The metabolome data of EOC patients were compared to those of the ToMMo cohort matched for age, height, weight, and BMI [ 45 , 46 ]. Data normalization was based on the median of gQC of each plate (four replicates/plate).…”
Section: Methodsmentioning
confidence: 99%
“…The metabolome data of EOC patients were compared to those of the ToMMo cohort matched for age, height, weight, and BMI [ 45 , 46 ]. Data normalization was based on the median of gQC of each plate (four replicates/plate).…”
Section: Methodsmentioning
confidence: 99%
“…Metabolic profiling in plasma samples has been widely performed via Kit-Met in several large-scale cohort studies, such as EPIC (European Prospective Investigation into Cancer and Nutrition) [ 30 , 43 , 44 ] and KORA (Cooperative Health Research in the Region of Augsburg) [ 31 ], and biomarker candidates have been reported to predict disease expression and progression when a previous version of this kit (AbsoluteIDQ p180 Kit, kit180) was used. In fact, kit180 stably quantified 110 metabolites in 10 μL plasma samples within a large-scale analysis in our previous study [ 38 ]. The current version, Kit-Met, increased the number of quantified metabolites by more than 600, and therefore, Kit-Met was utilized by the UHPLC-MS/MS system.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main goals of this cohort was to identify predictive biomarkers of disease expression for future precision medicine by using metabolic profiling techniques combined with other datasets, such as genomics, phenotypes, and/or habitudes [ 36 , 37 ]. During this large-scale cohort metabolic profiling project, forty-five metabolites from more than 30,000 plasma samples were analyzed by NMR, 110 metabolites from approximately 2000 plasma samples and 421 metabolites from approximately 2300 plasma samples were analyzed by Kit-Met [ 6 ], and their quantified values were included in the commercial database “Japanese Multi Omics Reference Panel, jMorp” [ 38 ]. The database has expanded both the number of samples and the number of quantified metabolites, and the quantified values from cohort participants could potentially be utilized as references for biomarker discovery studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, GAA genetic variants found in KRGDB (30× coverage group, 1465 individuals) were analyzed. In addition, the Japanese Multi Omics Reference Panel (jMorp, , accessed on 16 March 2021) was used to analyze GAA variants in the Japanese general population [ 6 , 7 ]. To date, the jMorp database contains the genomic data (whole-genome sequencing data) of 8380 Japanese individuals.…”
Section: Methodsmentioning
confidence: 99%